Pengaruh Persepsi Atas Lingkungan Sekolah Dan Motivasi Belajar Terhadap Prestasi Belajar Kewirausahaan Pada SMK Swasta Di Kabupaten Bogor - Neng Hastuti (Herodotus: Jurnal Pendidikan IPS, 2022)
The purpose of this study was to determine the effect of perceptions on the school environment and learning motivation on entrepreneurship learning achievement of students in private vocational schools in Bogor Regency. The research method used was a survey with correlation and regression analysis. The population of this study were students of private vocational schools in Bogor Regency with the sampling technique, namely random sampling. The sampling used in this study amounted to 92 people. From the results of the research data analysis obtained: (1) there is a significant effect of perceptions of the school environment and learning motivation together on the entrepreneurial learning achievement of students of private vocational schools in Bogor Regency, this is evidenced by the value of Sig = 0.005 < 0.05 and Fcount = 5,717. (2) there is a significant effect of perceptions of the school environment on student entrepreneurship learning achievement in private vocational schools in Bogor Regency, this is evidenced by Sig = 0.007 < 0.05 and tcount = 2.743. (3) There is no significant effect of learning motivation on student entrepreneurship learning achievement in private vocational schools in Bogor Regency, this is evidenced by Sig = 0.109 < 0.05 and tcount = 1.617. The results of this study are useful for improving entrepreneurship learning achievement of vocational students.